Supercomputing : second Russian Supercomputing Days, RuSCDays 2016, Moscow, Russia, September 26-27, 2016, Revised selected papers /: second Russian Supercomputing Days, RuSCDays 2016, Moscow, Russia, September 26-27, 2016, Revised selected papers. (2016) - Unknown
No abstract available